MAP: efficient cooperation induced routing scheme for a delay tolerant multi-hop mobile network. (2019) - Olakanmi, Oladayo O.; Kamil, Ismaila A.
In multi-hop network the efficiency of the transmission depends solely on the cooperation of all nodes in the network in relaying neighbouring nodes' data packets. Some nodes may be selfish, mischievous by dropping received packets or refuse to accept packet from other nodes whereas using other nodes resources to transmit their packets. This drastically affects the performance of the network. In this paper, a fair and effective incentive mechanism, which induces cooperation among nodes in the network is proposed. The mechanism applies auction scheme by initiating auction between the node and its immediate neighbouring nodes. The neighbouring node(s) competitively purchase packets transmission liability from the source and re-auctions it to the neighbouring node. The performance characterisation and evaluation against fairness and some possible attacks demonstrated that the scheme strongly stimulates fairness and competitiveness in message relaying among the intermediary nodes unlike other incentive based schemes.